2014
DOI: 10.1080/17452759.2014.913400
|View full text |Cite
|
Sign up to set email alerts
|

Part strength evolution with bonding between filaments in fused deposition modelling

Abstract: The present work investigates, by both mathematical modelling and experiment, the contribution of bonding between the filaments to the strength of the parts manufactured by fused deposition modelling (FDM). A mathematical model for neck growth between cylindrical filaments is derived based on viscous sintering for cylindrical filaments. Theoretical ultimate tensile load is determined from the layer thickness information and predicted average final neck size between filaments. The experimental ultimate tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(128 citation statements)
references
References 11 publications
6
120
0
2
Order By: Relevance
“…Thus, the result achieved for the tensile strength reflects more the effect of the in‐plane deformation through the −45°/+45° layups for which the intra‐layer bond is a major contributor in tensile response. The result obtained by Gurrala et al shows that the activation of the intra‐layer deformation mechanism (filaments aligned with the loading direction) leads to a ductile‐type failure against inter‐layer mechanism (layers normal to the loading direction), which enhances the brittle‐type failure. In addition, several studies demonstrate that the lowest tensile strength is achieved for vertical build orientation (loading direction aligned with the building direction) .…”
Section: Resultsmentioning
confidence: 98%
“…Thus, the result achieved for the tensile strength reflects more the effect of the in‐plane deformation through the −45°/+45° layups for which the intra‐layer bond is a major contributor in tensile response. The result obtained by Gurrala et al shows that the activation of the intra‐layer deformation mechanism (filaments aligned with the loading direction) leads to a ductile‐type failure against inter‐layer mechanism (layers normal to the loading direction), which enhances the brittle‐type failure. In addition, several studies demonstrate that the lowest tensile strength is achieved for vertical build orientation (loading direction aligned with the building direction) .…”
Section: Resultsmentioning
confidence: 98%
“…A temperature regulated extrusion head consists of liquefier nozzle that extrudes the semiliquid thermoplastic material and deposits in form of precise layers over a fixtureless base table [2]. The temperature inside the chamber is maintained lower than the melting temperature of the filament therefore, the deposited filament rapidly solidify when adhered to the previous layer thus involving highly transient heat transfer process [3].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of building direction and model interior on volumetric shrinkage and tensile strength was investigated for FDM parts using multi-objective optimization technique [13]. They further investigated the effect of inter-layer bonding, intra-layer bonding and neck formation between adjacent filaments on tensile strength of FDM parts using both experimental and mathematical modeling [14]. They observed that in a FDM sample with 0° raster layers the failure of a specimen is due to inter-layer fracture whereas in 45° raster layers, specimen fails under both inter-layer and intra-layer fracture.…”
Section: Introductionmentioning
confidence: 99%